Human Papilloma Virus Infection and Anal Squamous Intraepithelial Lesions - Svidler López, Laura; La Rosa, Luciana (Clinics in Colon and Rectal Surgery, 2019)
This article addresses the natural history of the human papilloma virus (HPV) infection to anal squamous intraepithelial lesions, and onto squamous cell carcinoma of the anus. This article provides overviews of the virology, pathophysiology, nomenclature, classification, historical terms, risk factors, clinical evaluation, differential diagnosis, and treatment of HPV infection and its sequelae.
Keywords: HPV; ASIL; HIV; PAIN; AIN; Bowen's disease; Bowenoid papulosis; squamous cell carcinoma